School Menu Review Programme (PReME): evaluation of compliance with dietary recommendations during the period 2006-2020 in Catalonia - Maria Blanquer-Genovart; Maria Manera-Bassols; Gemma Salvador-Castell; Oriol Cunillera-Puértolas; Conxa Castell-Abat; Carmen Cabezas-Peña (BMC, 2022)
Abstract Background The School Menu Review Programme (PReME) has been offering complimentary revisions of meal plans to all schools in Catalonia since 2006. This study aims to assess the evolution of compliance with PReME's recommendations in the meals provided by school cafeterias in Catalonia during the period 2006-2020. Methods Pre-post study with a sample of 6,387 meal plans from 2221 schools assessed during the period. The information was collected mainly by public health specialists within the annual technical and sanitary inspection of school kitchens and cafeterias. Meal plans were evaluated by Dietitian-Nutritionists team according to the criteria of the National Health System's "Consensus document on nutrition in schools" and the Public Health Agency of Catalonia's current guide "Healthy eating at school". Reports were sent to each participating school. A few months later, a new meal plan and another questionnaire were collected and evaluated in comparison with the first meal plan. Compliance with the recommendations was analysed based on the type of canteen management and the school category. Results Compliance improved during the study period. The percentage of schools that complied with dietary recommendations in relation to the five PReME indicators (fresh fruit, pulses, daily vegetables, fresh food and olive oil for dressing) has steadily increased since PReME began, (over 70% in all indictors; p =  < 0.001), with variations depending on school category and cafeteria management. Furthermore, an improvement in the levels of compliance with de recommended food frequencies was observed. with statistically significant differences for all items (p < 0.001), except for pulses whose compliance had been high since the beginning of the study (p = 0.216). Conclusions The positive evolution in compliance with PReME's recommendations provides evidence of the programme's effectiveness, with an improvement in the quality of school meals delivered in Catalonia.